OPTIMALISASI PENGUATAN KARAKTER SISWA SEKOLAH DASAR MELALUI METODE PEMBELAJARAN JOFULL LEARNING BERBASIS MEDIA SABAQU FOR MUSLIM KIDS - Laela, Umrotul; Basukiyatno; Tity Kusrina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Character education is a fundamental aspect of shaping students’ personalities from an early age, particularly at the elementary school level. This study aims to explore the relevance and effectiveness of implementing the joyfull learning method integrated with the sabaqu for muslim kids media in strengthening students’ character values such as self-confidence, cooperation, discipline, and independence. Joyfull learning emphasizes happiness, active engagement, and a joyful classroom atmosphere as the core of the learning process, while sabaqu media is designed to internalize Islamic character values through contextual and meaningful educational games. Using a descriptive qualitative approach, data were collected library research. The findings reveal that the synergy between joyfull learning and sabaqu media creates a learning process that is not only enjoyable but also effective in holistically developing students’ character. These results offer valuable implications for teachers, curriculum developers, and educational institutions to adopt learning models that align academic, moral, and emotional aspects of students.